2014
DOI: 10.1515/ract-2013-2193
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of Np(V) oxidation to Np(VI) in 3 mol/dm3 nitric acid at elevated temperatures

Abstract: Optical absorption spectra of Np in 3 mol/dm 3 nitric acid at elevated temperatures were measured using an optical glass cell with a water jacket having a light path of 1 cm. Molar extinction coefficients of Np(VI), T M −1 cm −1 , were obtained at various temperatures (297, 313, 334, 352, and 372 K). The values of T were found to decrease with increasing temperature and could be described by the equation T = −0.14 + 85.5, where is the temperature. Oxidation of Np(V) to Np(VI) in 3 M nitric acid at elevated tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Interestingly, Np(VI) concentration did not increase with increasing temperature despite literature reports that suggest otherwise. 13 A possible explanation is the relatively low acidity (1 M HNO 3 ) in these experiments. These fluctuations could arise from alterations of the primary or secondary hydration sphere surrounding the Np(V) ion.…”
Section: Vis-nir Absorption Spectra and Derivativesmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, Np(VI) concentration did not increase with increasing temperature despite literature reports that suggest otherwise. 13 A possible explanation is the relatively low acidity (1 M HNO 3 ) in these experiments. These fluctuations could arise from alterations of the primary or secondary hydration sphere surrounding the Np(V) ion.…”
Section: Vis-nir Absorption Spectra and Derivativesmentioning
confidence: 88%
“…Studies over the last seven decades have measured Vis-NIR absorption and Raman spectral signatures of various oxidation states of Np in aqueous solutions. [5][6][7][8][9][10][11][12][13] Aqueous absorption spectra of Np(V) and Np(VI) ions have even been characterized to determine electronic structural, optical, and magnetic properties using ab initio calculations. 14,15 The intense 980 nm (Є = 395 M -1 •cm -1 ) band and a less intense band at 616 nm (Є = 22 M -1 •cm -1 ) are commonly used to determine Np concentration in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported characteristic electronic spectra of Np oxidation states ranging from Np(III) to Np(VI). (Sjoblom and Hindman, 1951;Ryan, 1960;Friedman and Toth, 1980;Ban et al, 2014;Chatterjee et al, 2017;Sadergaski and Morgan, 2022). However, similar redox potentials, differing chemical and redox behavior, the ability to react with certain complexing ligands, and differing stabilities in acid of various concentrations all contribute to the complex redox chemistry of Np and the difficulty in acquiring electronic spectra of single oxidation states.…”
Section: Np Vis/nir Absorption Spectramentioning
confidence: 99%
“…A broad system of overlapping peaks occurred near 555 nm, and the most characteristic feature of the Np(VI) spectrum is an asymmetric peak that occurs in the NIR region near 1,223 nm. (Ban et al, 2014).…”
Section: Np Vis/nir Absorption Spectramentioning
confidence: 99%
See 1 more Smart Citation